PENERAPAN STRATEGI BELAJAR AKTIF TIPE LISTENER TEAM MENGGUNAKAN MEDIA MICROSOFT POWERPOINT DALAM PEMBELAJARAN MATEMATIKA KELAS VIII MTsN LUBUK BUAYA PADANG - Antoni Rahman; Muhammad Arif; Sefrinal Sefrinal; Efendi Efendi; Okviani Syafti (STKIP Pesisir Selatan, 2021)
The mathematics learning outcomes of most of the VIII grade students of MTsN Lubuk Buaya have not reached the Minimum Completeness Criteria. One of the efforts that can be made by the teacher to activate students in learning which can improve student learning outcomes is to apply an active learning strategy of the Listener Team type using Microsoft Powerpoint media. The purpose of this study was to determine the activities and learning outcomes of students' mathematics by implementing an active learning strategy of Listening Team type using Microsoft Powerpoint media. This research is a quasi-experimental research. The population of this study were students of class VIII MTsN Lubuk Buaya. The sampling technique was done by drawing numbers and the selected samples were students of class VIII.2 as the experimental class and class VIII.3 as the control class. The data were first tested for normality, homogeneity test and analysis of variance. The results showed that the mathematics learning outcomes of students who used the application of the Listener Team type active learning strategy using Microsoft Powerpoint media were better than conventional learning in class VIII MTsN Lubuk Buaya. The student activity data was obtained through observations at each meeting in the experimental class which showed that students' mathematics learning activities increased after being taught by implementing an active learning strategy of Listening Team type using Microsoft Powerpoint media in class VIII MTsN Lubuk Buaya.